KEKURANGAN PERSIAPAN YAYASAN DALAM MEMBANGUN PENDIDIKAN DI TK AR RAHMAN - Mahfudza, Amalia; Zaskia Siregar, Fatimah Nayla; Munadia, Khairani; Afifah, Zahra (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini (PGPAUD), 2023)
In the learning preparation process, the school or foundation needs to prepare learning activities at school. Things that must be prepared are such as adequate school facilities, then the teacher's method of teaching. The importance of having school facilities for the convenience of students in the learning process, in this case it is necessary to develop existing facilities at the school. For the learning process, there is also a need for teacher supervision of children in learning and outside the classroom, because teacher supervision of children is needed by students in their activities while at school. Supervision can be interpreted as a process of monitoring activities to ensure that all organizational operations are carried out as intended and the process of correcting deviations that will hinder the achievement of objectives. For teachers, absence from teaching according to schedule is sometimes unavoidable, considering that one time they had a sudden need at the same time so they did not teach. However, this becomes unnatural if the absence or delay of teaching in class always and frequently occurs. This has a negative impact on the learning process. First, students become disillusioned, and this can reduce their learning motivation. Students get a bad example of discipline. Second, teachers who teach earnestly feel that their efforts are futile and at the same time disappointed. What they built was broken by their professional colleagues. Not to mention, if a teacher who is disciplined in teaching earns the same income as a teacher who rarely teaches in class. A teacher can be called a professional if he has 4 (four) competencies, namely pedagogical competence, professional competence, personality competence, and social competence. The researcher uses qualitative data analysis techniques, because this study uses many words instead of numbers. Therefore, we use qualitative data analysis techniques.